The Effecttiviness of using Android-Based Social Science Learning Media to Increase Student Knowladge Competence - Uskur Nikmawati; Ine Kusuma Aryani; Sri Khusnul Wahyu Yuliani (UM Purwokerto Press, 2023)
This study aims to increase students' knowledge competence in social studies material, especially in Indonesian Cultural Diversity material after using social studies learning media based on Android for class IV at SD UMP. the research method used is classroom action research with four main stages of classroom action research models namely: planning, implementing, observing, and reflecting. The results of the study show that the existence of social studies learning media based on Android has succeeded in increasing students' knowledge competence related to Indonesian Cultural Diversity material. Based on the competence of students' knowledge by using social studies learning media based on Android, it was found that the pretest target was 25% of students complete while the posttest was 100% of students complete.